A low-carbon mass concrete and its preparation process
By using specific raw materials and processes in large volume concrete to form a cross-linked network structure and absorbing hydration heat, the problem of large volume concrete being prone to temperature cracks is solved, and its crack resistance and strength are significantly improved.
Patent Information
- Application Number
- CN202311226478.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-09-22
Smart Images

Figure GDA0005089474240000061 
Figure GDA0005089474240000071
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of building materials, and more specifically, to a low-carbon mass concrete and a preparation process thereof. Background Art
[0002] Modern buildings often involve large-volume concrete construction, such as high-rise building foundations, large equipment foundations, water conservancy dams, etc. Its main feature is its large volume, and the minimum size of the smallest section in any direction is 1m.
[0003] During the pouring of mass concrete, cement reacts with water and releases a large amount of heat. As the heat increases, the surface temperature of the mass concrete is released in time, while the internal temperature cannot be released in time, resulting in an increase in the temperature difference between the inside and the outside. In the early stage of cement pouring, due to the low elastic modulus and strength of the mass concrete, its constraint stress is also small, so no temperature cracks will appear at this stage. As the cement pouring continues, the age of the mass concrete increases, and the elastic modulus and strength increase accordingly, resulting in an increase in the deformation constraint of the mass concrete, which increases the temperature stress inside the mass concrete structure. When the temperature stress exceeds the tensile strength, cracks will appear, causing temperature cracks in the mass concrete. According to current construction technology, temperature cracks will appear on the surface of mass concrete and in the internal structure of mass concrete, and the crack widths are also different. Generally, the crack widths caused by the small temperature difference in summer are also smaller, while the cracks caused by the large temperature difference in winter are also larger. Because the temperature difference between winter and summer further causes damage to the mass concrete, it affects the safety and normal use of the building structure. Summary of the invention
[0004] In order to improve the crack resistance of mass concrete, the present application provides a low-carbon mass concrete and a preparation process thereof.
[0005] In a first aspect, the present application provides a low-carbon mass concrete, which adopts the following technical solution:
[0006] A low-carbon mass concrete comprises the following raw materials in parts by weight:
[0007] 20-25 parts of Portland cement, 10-15 parts of fly ash, 16-20 parts of lime powder, 6-8 parts of polyvinyl alcohol, 3-8 parts of cross-linking agent, 4-8 parts of amino-modified polysiloxane, 4-6 parts of quartz sand, and 40-45 parts of water.
[0008] By adopting the above technical scheme, the hydration heat of silicate cement in the presence of slag is low, polyvinyl alcohol absorbs water during cement hydration to produce condensation reaction to release low molecules, reacts with polysiloxane to produce a hydrophilic copolymer with carbon as the main chain and siloxane as the side chain, and the chain segments are cross-linked and cured to form a cross-linked network structure, which improves the tensile strength of concrete to resist the internal stress caused by temperature difference and prevents the occurrence of cracks. The amino groups carried on it react with the alkaline substances produced in the hydration process to absorb part of the heat in the cement hydration process, reduce the hydration heat, generate more calcium ions to react with silicate colloid in the hydration product, form more hardening products, accelerate the hardening speed of concrete, improve the strength of concrete, make concrete have good anti-shrinkage performance, avoid the occurrence of cracks, and the calcium ions can combine with the hydroxide ions in the hydration product to form a dense substance, improve the compactness and durability of concrete, and further improve the tensile strength of concrete.
[0009] In the present application, silicate cement which produces less hydration heat is selected, fly ash, lime powder and quartz sand are added as fillers to replace part of the cement, thereby reducing the release of carbon dioxide in the concrete. At the same time, the lime powder absorbs carbon dioxide during the solidification process to undergo carbonization and harden, thereby achieving low-carbon concrete. In addition, the lime powder and fly ash have low shrinkage, thereby further improving the splitting tensile properties of the concrete.
[0010] Optionally, the amino-modified polysiloxane is prepared by the following steps:
[0011] (1) mixing polysiloxane and diethylenetriamine in a certain mass ratio, adding isopropyl alcohol and tris(hydroxymethyl)aminomethane, heating and reacting for a period of time, and then distilling under reduced pressure to obtain a preliminary reaction product;
[0012] (2) The preliminary reaction product is mixed with a nonionic emulsifier to obtain the modified polysiloxane.
[0013] By adopting the above technical solution, the primary and secondary amine groups of the diethylenetriamine molecule have high reactivity, and are grafted into the polymethylsilane segment together with trihydroxymethylaminomethane, and the initial reaction product of the modified polysiloxane is formed through condensation reaction. The obtained product is mixed with an emulsifier to make the modified polysiloxane have good dispersibility and stability, which is conducive to its mixing and reaction in concrete. Good dispersibility is also conducive to giving full play to the good heat dissipation performance of polysiloxane, further reducing the temperature difference between the inside and outside of the concrete, reducing the stress caused by temperature, and preventing cracks in the concrete.
[0014] Optionally, the weight ratio of the polysiloxane, diethylenetriamine and tris(hydroxymethyl)aminomethane is (1.5-2):1:1.
[0015] By adopting the above technical solution, the modified polysiloxane prepared within this range has a good conversion rate. Exceeding this ratio will lead to waste of reaction raw materials or be unfavorable for the synthesis of modified polysiloxane.
[0016] Optionally, the nonionic emulsifier is fatty alcohol polyoxyethylene ether.
[0017] Optionally, the mass ratio of the preliminary reaction product to the non-ionic emulsifier is (2-2.5):1.
[0018] By adopting the above technical solution, the ether bonds contained in the fatty alcohol polyoxyethylene ether increase the hydrophilicity of the polysiloxane, so that the modified polysiloxane has good dispersion uniformity and stability, which is beneficial to further improve the compressive properties of concrete.
[0019] Optionally, the cross-linking agent is any one of sodium aluminate and aluminum oxide.
[0020] By adopting the above technical solution, sodium aluminate and aluminum oxide can react with the polymer to form a cross-linked structure, thereby improving the strength and durability of the concrete. At the same time, sodium aluminate and aluminum oxide can also conduct heat through the nonlinear thermal vibration of the crystal, so that the hydration heat generated inside the cement can be quickly dispersed, reducing the temperature difference between the inside and outside of the concrete and avoiding the occurrence of cracks.
[0021] Optionally, the raw material also includes 5-8 parts of diamond powder.
[0022] The addition of diamond powder improves the heat conduction of internal components while further improving the density and stability of concrete and increasing the compressive strength of concrete.
[0023] In a second aspect, the present application provides a process for preparing low-carbon mass concrete, which adopts the following technical solution: A process for preparing low-carbon mass concrete, comprising the following preparation steps:
[0024] (1) weighing various raw material components, adding polyvinyl alcohol, amino-modified polysiloxane, a crosslinking agent, and half of the water, and mixing and stirring to obtain a primary mixture;
[0025] (2) Adding silicate cement, lime powder, fly ash, quartz sand and the remaining water to the primary mixture and stirring to obtain the low-carbon mass concrete.
[0026] By adopting the above technical solution, other fillers are added and stirred for reaction after the initial reaction of polyvinyl alcohol and amino-modified polysiloxane, which is conducive to better adhesion of various components in the network structure and improves the compressive strength of concrete.
[0027] In summary, this application has the following beneficial effects:
[0028] 1. Since the application adopts the addition of lime powder and fly ash to reduce the amount of cement, the hydration heat generated by cement is reduced to a certain extent, the temperature stress of concrete is reduced, polyvinyl alcohol and amino-modified polysiloxane produce a polymerization reaction, and the chain segments are cross-linked and cured to form a network structure, which resists the temperature stress inside the concrete and further enhances the crack resistance of the concrete.
[0029] 2. In the present application, modified polysiloxane is preferably used. Polysiloxane has good thermal conductivity. The modified polysiloxane has good dispersibility and stability, and can be evenly dispersed in concrete, effectively reducing the temperature difference between the inside and outside of the concrete, reducing the stress caused by temperature, and improving the crack resistance of the concrete.
[0030] 3. The present application further selects sodium aluminate and aluminum oxide with good thermal conductivity as cross-linking agents to participate in the cross-linking reaction of polyvinyl alcohol and polysiloxane, further reducing the temperature difference between the inside and outside of the concrete and improving the crack resistance of the concrete. DETAILED DESCRIPTION
[0031] The present application is further described in detail below with reference to the embodiments.
[0032] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0033] Preparation examples of raw materials and / or intermediates
[0034] Preparation Example 1
[0035] An amino-modified polysiloxane, the preparation of which comprises the following steps:
[0036] (1) 12 kg of polysiloxane and 8 kg of diethylenetriamine were mixed, 5 kg of isopropanol and 8 kg of tris(hydroxymethyl)aminomethane were added, heated to 75° C. and reacted for 4 hours, and then the solvent was removed by distillation under reduced pressure to obtain a preliminary reaction product;
[0037] (2) 10 kg of the preliminary reaction product and 5 kg of a nonionic emulsifier, distearate, were mixed and stirred to obtain the modified polysiloxane.
[0038] Preparation Example 2
[0039] An amino-modified polysiloxane, which is different from Preparation Example 1 in that the nonionic emulsifier used in this Preparation Example is fatty alcohol polyoxyethylene ether.
[0040] Preparation Example 3
[0041] An amino-modified polysiloxane, which is different from Preparation Example 2 in that the preparation comprises the following steps:
[0042] (1) 13 kg of polysiloxane and 7.5 kg of diethylenetriamine were mixed, 5 kg of isopropanol and 7.5 kg of tris(hydroxymethyl)aminomethane were added, heated to 75° C. and reacted for 4 hours, and then the solvent was removed by distillation under reduced pressure to obtain a preliminary reaction product;
[0043] (2) 10 kg of the preliminary reaction product and 4 kg of nonionic emulsifier fatty alcohol polyoxyethylene ether were mixed and stirred to obtain the modified polysiloxane.
[0044] Preparation Example 4
[0045] An amino-modified polysiloxane, which is different from Preparation Example 2 in that the preparation comprises the following steps:
[0046] (1) 14 kg of polysiloxane and 7 kg of diethylenetriamine were mixed, 5 kg of isopropanol and 7 kg of tris(hydroxymethyl)aminomethane were added, heated to 75° C. and reacted for 4 hours, and then the solvent was removed by distillation under reduced pressure to obtain a preliminary reaction product;
[0047] (2) 10 kg of the preliminary reaction product and 5 kg of nonionic emulsifier fatty alcohol polyoxyethylene ether were mixed and stirred to obtain the modified polysiloxane.
[0048] Comparative Preparation Example 1
[0049] An amino-modified polysiloxane, the preparation of which comprises the following steps:
[0050] (1) 16.8 kg of polysiloxane and 5.6 kg of diethylenetriamine were mixed, 5 kg of isopropanol and 5.6 kg of tris(hydroxymethyl)aminomethane were added, heated to 75° C. and reacted for 4 hours, and then the solvent was removed by distillation under reduced pressure to obtain a preliminary reaction product;
[0051] (2) 10 kg of the preliminary reaction product and 5 kg of a nonionic emulsifier, distearate, were mixed and stirred to obtain the modified polysiloxane.
[0052] Example
[0053] Example 1
[0054] A low-carbon mass concrete, the preparation of which comprises the following steps:
[0055] (1) weighing various raw material components, adding 7 kg of polyvinyl alcohol, 6 kg of amino-modified polysiloxane, 5.5 kg of a crosslinking agent, and 20 kg of water, and mixing and stirring to obtain a primary mixture;
[0056] (2) Add 20 kg of Portland cement, 18 kg of lime powder, 12.5 kg of fly ash, 4 kg of quartz sand and the remaining water to the primary mixture and stir to obtain the low-carbon mass concrete. In this example, the amino-modified polysiloxane prepared in Preparation Example 1 is used, and boric acid is used as a crosslinking agent.
[0057] Example 2-3
[0058] A low-carbon mass concrete, which is different from Example 1 in that the raw material components and their corresponding weight proportions are shown in Table 1.
[0059] Table 1 Raw materials and their weights in Examples 1-3 (kg)
[0060] Example 1 Example 2 Example 3 Polyvinyl alcohol 7 8 6 Amino modified polysiloxane 6 4 8 Crosslinking agent 5.5 3 8 Portland cement 20 22.5 25 Lime powder 18 16 20 Fly ash 12.5 15 10 Quartz sand 4 5 6 water 40 42.5 45
[0061] Example 4
[0062] A low-carbon mass concrete, which is different from Example 1 in that the amino-modified polysiloxane used in this example is prepared in Preparation Example 2.
[0063] Example 5
[0064] A low-carbon mass concrete, which is different from Example 1 in that the amino-modified polysiloxane used in this example is prepared in Preparation Example 3.
[0065] Example 6
[0066] A low-carbon mass concrete, which is different from Example 1 in that the amino-modified polysiloxane used in this example is prepared in Preparation Example 4.
[0067] Example 7
[0068] A low-carbon mass concrete, which is different from Example 6 in that the cross-linking agent used in this example is sodium aluminate.
[0069] Example 8
[0070] A low-carbon mass concrete, which is different from Example 6 in that the cross-linking agent used in this example is aluminum oxide.
[0071] Example 9
[0072] A low-carbon mass concrete, which is different from Example 8 in that this embodiment also includes 5 kg of diamond powder. The preparation includes the following steps:
[0073] (1) weighing various raw material components, adding 7 kg of polyvinyl alcohol, 6 kg of amino-modified polysiloxane, 5.5 kg of a crosslinking agent, and 20 kg of water, and mixing and stirring to obtain a primary mixture;
[0074] (2) Add 20 kg of silicate cement, 18 kg of lime powder, 12.5 kg of fly ash, 4 kg of quartz sand, 5 kg of diamond powder and the remaining water to the primary mixture and stir to obtain the low-carbon mass concrete.
[0075] Comparative Example
[0076] Comparative Example 1
[0077] A low-carbon mass concrete, which is different from Example 1 in that the amino-modified polysiloxane prepared in Comparative Preparation Example 1 is used in this comparative example to replace the amino-modified polysiloxane in Example 1.
[0078] Comparative Example 2
[0079] A low-carbon mass concrete, which is different from Example 1 in that unmodified polysiloxane is used in this comparative example.
[0080] Comparative Example 3
[0081] A low-carbon mass concrete, which is different from Example 1 in that polyvinyl alcohol is not added in this comparative example.
[0082] Performance testing
[0083] Testing method: Hydration heat: The hydration heat of the sample is determined according to the direct method of GB / T 12959-2008 "Method for determination of hydration heat of cement". The temperature change in the concrete at room temperature is measured by a calorimeter, and the sum of the heat accumulated and dissipated in the calorimeter is calculated to obtain the hydration heat of cement after 3 days and 7 days of curing.
[0084] Split tensile strength and compressive strength test: The splitting tensile strength and compressive strength of concrete are measured according to the method described in GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete";
[0085] Crack resistance: The ring restraint test is used to test the crack resistance of concrete: cracking time <1h is very poor cement, and cracking time >15h is excellent.
[0086] Table 2 Performance test results
[0087]
[0088]
[0089] Combining Examples 1-3 and Comparative Example 1 and Table 2, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 1, indicating that the modified polysiloxane prepared using this solution has good heat dissipation performance, which is beneficial to reducing the temperature difference between the inside and outside of the concrete, reducing the stress caused by temperature, and is beneficial to improving the crack resistance and compressive resistance of the concrete.
[0090] Combining Examples 1-3 and Comparative Example 2 and Table 2, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 2, and the compressive strength of concrete made from unmodified polysiloxane is greatly reduced, affecting the final performance of the concrete.
[0091] Combining Examples 1-3 and Comparative Example 3 and Table 2, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 3. When polyvinyl alcohol is not added, a stable network structure cannot be formed in the concrete to improve the compression and crack resistance of the concrete, resulting in a significant decrease in the splitting tensile strength and compressive strength of the concrete.
[0092] Combining Examples 1-6 and Table 2, it can be seen that the experimental data of Examples 4-6 are better than those of Examples 1-3. The difference between Example 4 and Example 1 is that the nonionic emulsifier used in Example 4 is fatty alcohol polyoxyethylene ether, which shows that the selection of emulsifier affects the final performance of concrete. By improving the dispersibility and stability of modified polysiloxane, the compression and crack resistance of concrete are improved.
[0093] Combining Example 6 with Examples 7-8 and Table 2, it can be seen that the experimental data of Examples 7-8 are better than those of Example 6, indicating that when the selected cross-linking agent is sodium aluminate or aluminum oxide, not only the compressive strength of the concrete can be improved, but also the dispersion rate of the hydration heat inside the concrete can be increased, thereby reducing the temperature stress inside the concrete, which is beneficial to improving the crack resistance of the concrete.
[0094] Combining Examples 8-9 and Table 2, it can be seen that the various test data of Example 9 are better than those of Example 8, indicating that adding diamond powder is beneficial to improving the compactness and stability of concrete, increasing the heat conduction efficiency of concrete, and thus obtaining concrete with good crack resistance.
[0095] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A low-carbon mass concrete, characterized in that: The composition comprises the following raw materials in parts by weight: 20-25 parts of Portland cement, 10-15 parts of fly ash, 16-20 parts of lime powder, 6-8 parts of polyvinyl alcohol, 3-8 parts of cross-linking agent, 4-8 parts of amino-modified polysiloxane, 4-6 parts of quartz sand, and 40-45 parts of water; the amino-modified polysiloxane is prepared by the following steps: (1) Mixing polysiloxane and diethylenetriamine in a certain mass ratio, adding isopropanol and tris(hydroxymethyl)aminomethane, heating and reacting for a period of time, and then distilling under reduced pressure to obtain a preliminary reaction product; (2) mixing the above-mentioned preliminary reaction product with a nonionic emulsifier to obtain the modified polysiloxane; The weight ratio of the polysiloxane, diethylenetriamine and tris(hydroxymethyl)aminomethane is (1.5-2):1:
1.
2. The low-carbon mass concrete according to claim 1, characterized in that: The nonionic emulsifier is fatty alcohol polyoxyethylene ether.
3. The low-carbon mass concrete according to claim 1, characterized in that: The added mass ratio of the preliminary reaction product to the non-ionic emulsifier is (2-2.5):
1.
4. The low-carbon mass concrete according to claim 1, characterized in that: The cross-linking agent is any one of sodium aluminate and aluminum oxide.
5. The low-carbon mass concrete according to claim 1, characterized in that: The raw materials also include 5-8 parts of diamond powder.
6. A process for preparing low-carbon mass concrete according to any one of claims 1 to 4, characterized in that: The method comprises the following preparation steps: (1) Weighing each raw material component, adding polyvinyl alcohol, amino-modified polysiloxane, a crosslinking agent and half of the water, and mixing and stirring to obtain a primary mixture; (2) Adding silicate cement, lime powder, fly ash, quartz sand and the remaining water to the primary mixture and stirring to obtain the low-carbon mass concrete.
Citation Information
Patent Citations
High-ductility low-shrinkage anti-cracking concrete for bridge deck pavement and preparation method thereof
CN102976697A
High-dispersion and high-adhesion shield grouting material
CN112194432A